1322. Infectious Complications Following Pediatric Lawn Mower Injury: A Case Series. (15th December 2022) - Weslander, Erin; Doyle, Joshua D; Nowalk, Andrew; Bykowski, Michael
Abstract: Background: According to the National Electronic Injury Surveillance System, there are an estimated 9, 400 riding lawn mower injuries in the United States in pediatric patients per year. Previous case series report a 7-12.5% infection rate after injury. We report our experience of lawn mower injury-related infections over a 4-year period. Methods: Cases of lawn mower injury at our center were identified by the ICD-10 code W28.XXXA for contact with a powered lawn mower between 2017-2020. Patient demographics, injury background, microbial results, and antimicrobial use were collected via manual chart review. Results: During the 4-year period, 25 patients presented to UPMC Children's Hospital of Pittsburgh who had a diagnosis of lawn mower injury. The median age of the patients was 6.5 years old. Most cases sustained foot injury (68%, 17/25), followed by leg (24%, 6/25), and hand or arm (24%, 6/25). Perioperative antibiotics depended on the extent of the damage, intent to amputate or salvage a limb, and extent of obvious contamination. These included 24-48 hours of piperacillin-tazobactam for 44% (11/25) of patients, ampicillin/sulbactam for 32% (8/25) of patients, and cefazolin for 24% (6/25) patients. Four of the 25 patients (16%) had infection after the initial injury as defined as growth of organisms from a wound culture collected more than 48 hours after the initial injury and debridement. Antimicrobials for the treatment of infection were further tailored to the culture results. From the four patients with infection after initial debridement or amputation, pathogens included: Serratia marcescens, Staphylococcus aureus, Myroides odartus, Stenotrophomonas, Prevotella, Aeromonas, Coagulase negative Staphylococcus, Enterobacter cloacae, Sphingomonas, Bacillus species, Pseudomonas aeruginosa, Candida albicans, Rhizopus, and Trichosporon. Conclusion: Infections after lawn mower injures are infrequent with early, aggressive surgical debridement. However, infections following lawn mower injuries are frequently polymicrobial and involve a wide variety of pathogens. Obtaining repeat cultures during subsequent surgical debridements can be useful to track persistent growth and identify new and uncommon pathogens. Disclosures: All Authors : No reported disclosures.